Review of Secure Patient Record Storage in Cloud Using Encryption and Decryption Method - A.Vikram, Dr.Gopinath Ganapathy (International Journal of Advanced Science and Technology, 2020)
Continuous developments in digital communication and information technology make the exchange of medical data considerably easier. E-health schemes are currently used and various well-known medical centres rely on them to transmit and receive medical information on the Internet and LAN. In recent years, there are various security schemes have been introduced to care for patient data confidentiality and ensure the security of the medical data exchanged. When communicating on unsafe storage media such as the Internet, it is essential to ensure the confidentiality of data shared with others. Some existing method parameters and metrics used to assess the cryptographic methods implemented have been considered. This following study explain a limitations and recent trends in the use of medical encryption. Lastly, the decisions of this review editorial are suggested with specificproposals for future research in this area. Keyword: Encryption, Decryption, Medical Data Protection, Cryptography, Symmetric and Asymmetric keys.